2020
DOI: 10.1155/2020/5363849
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients with Acromegaly before and after Transsphenoidal Surgical Resection

Abstract: Objective. We aimed to determine the perioperative changes in the quality of life (QoL) in patients with acromegaly and to reveal the relationship between biochemical indicators and quality of life change after tumor resection. Methods. Patients with acromegaly were enrolled from a tertiary pituitary center. SF-36 scale and AcroQoL scale were used to determine the QoL before and after surgery. We analyzed changes in QoL using a generalized linear model for repeated measurements. We compared the changes in QoL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…In contrast, other studies show a different view; in Shanghai, China, Gu et al (2020) concluded that improvement in HrQoL was achieved in acromegaly patients treated by transsphenoidal surgery independent of biochemical control [ 24 ]. Negger et al (2008) found in their prospective, double-blind placebo-controlled study on 20 patients on SRLs therapy that there is an improvement in their HrQoL after adding pegvisomant to SRLs with no significant reduction even in patients with controlled baseline IGF-1 level [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies show a different view; in Shanghai, China, Gu et al (2020) concluded that improvement in HrQoL was achieved in acromegaly patients treated by transsphenoidal surgery independent of biochemical control [ 24 ]. Negger et al (2008) found in their prospective, double-blind placebo-controlled study on 20 patients on SRLs therapy that there is an improvement in their HrQoL after adding pegvisomant to SRLs with no significant reduction even in patients with controlled baseline IGF-1 level [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…1), of which seven reported absolute values. In these seven studies, scores of refractory acromegaly patients compared to patients in remission varied substantially, described as either comparable in the two patient groups in four studies [44][45][46][47], decreased in one study [38], or decreased except for the domain personal relations in another study [48] (Table 1). One study compared refractory acromegaly patients to healthy controls, finding lower scores in all domains for refractory patients [49].…”
Section: Disease-specific Hr-qolmentioning
confidence: 99%
“…AcroQoL Acromegaly Quality of Life Questionnaire, IQR interquartile range, SMS( +) on somatostatin analogue treatment, SMS(−) not on somatostatin analogue treatment, ↓ significantly lower compared to acromegaly patients in remission; ↑ significantly higher compared to acromegaly patients in remission, no P-value reported, = tested and no significant difference compared to patients in remission a Patients received octreotide LAR every two weeks (dose not reported) b Psychological subscales c AcroQoL scores did not differ between refractory patients and patients in remission at 24 weeks d No significant difference between all refractory patients SMS (+) or SMS (−) and patients in remission. No subgroup analysis performed for SMS(+) and SMS(−) separately e Refractory patients scored significantly lower than healthy controls f Values estimated based on figure, absolute values were not presented g Patients received weekly intramuscular injections of octreotide LAR 20 mg. At 12 weeks a dose escalation to octreotide LAR 30 mg was permitted in case GH > 2.5 ug/L and/or IGF1 above upper limit of normal for age, but this was not obligatory Chin [47] Gu [44] Guo [38] Hua [46] Psaras [49] Trepp [48] Yamamoto [45] Guo [38] SF-12 Psaras [49] Alcalar [54] Nader [50] d Psaras [49] Vega-Beyhart [52] Ye [53]…”
Section: Disease-specific Hr-qolmentioning
confidence: 99%
See 1 more Smart Citation
“…Another relevant application of the questionnaire is to compare the effects of different treatments. Among the most recent studies in this regard is the one conducted by Gu et al in 2020 [ 10 ]. Designed to evaluate the effectiveness of transsphenoidal neurosurgical therapy on patients’ quality of life, this analysis shows the improvement of patients’ quality of life after surgery, and, additionally, that this enhancement is incomplete and independent from the endocrinological remission of the disease.…”
Section: Patient-reported Outcome (Pro) Toolsmentioning
confidence: 99%